Uji Aktivitas Antibakteri Kombinasi Ekstrak Daun Salam (Syzygium polyanthum (Wight) Walp.) Dengan Daun Kemangi (Ocimum x africanum L.) Terhadap Pertumbuhan Bakteri Streptococcus mutans - Riza Dwiningrum; Wina Safutri; Mida Pratiwi; Lintang Sevira (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Dental caries infection is one of the most common dental health problems and is caused by the activity of Streptococcus mutans bacteria. Treatment typically involves antibiotics, but irrational use of antibiotics can lead to resistance. Therefore, the development of natural-based treatments is needed. One of the plants utilized for this purpose is bay leaf (Syzygium polyanthum) and basil leaf (Ocimum × africanum). This research objective is to examine the antibacterial activity of the combination of bay leaf and basil leaf extracts against the growth of Streptococcus mutans. The research is a quantitative experimental laboratory study. The bay and basil leaves were extracted using maceration with 96% ethanol as the solvent, followed by phytochemical screening. Antibacterial testing toward Streptococcus mutans was conducted using the disc diffusion method with concentration ratios of 50%:50%, 60%:40%, and 70%:30%. Phytochemical screening of both extracts revealed the presence of flavonoids, saponins, tannins, and alkaloids. The results of the antibacterial test showed that the combination of bay leaf and basil leaf extracts exhibited antibacterial activity, indicated by the formation of clear zones around the paper discs, with average inhibition zone diameters of 6.15 mm (PI: 50%:50%), 8.8 mm (PII: 60%:40%), and 9.47 mm (PIII: 70%:30%), categorized as moderate activity. Based on a One-Way ANOVA test, a significance value of 0.000 (<0.05) indicated a significant difference among the different extract concentrations in inhibiting Streptococcus mutans. Further analysis using Tukey’s HSD test showed that the PIII treatment (70%:30%) differed significantly compared to the other treatment groups. In conclusion, the combination of bay leaf and basil leaf extracts has potential as an antibacterial agent against the growth of Streptococcus mutans.